Perceived Impacts of a Public Health Training Center Field Placement Program among Trainees: Findings from a Small Group Externship Experience - Johansson, Patrik; Grimm, Brandon; Abdel-Monem, Tarik; Hoffman, Stacey J.; DeKraai, Mark; McMillan, Analisa (Frontiers in Public Health, 2014)
There is heightened interest in identifying the impact of the federally-funded Public Health Training Center (PHTC) program. Although evaluation studies have been conducted of public health training in general, evaluations of PHTC programs are rare. Field placement components are Congressionally-mandated requirements of PHTCs. Field placements are typically intensive, supervised externships for students to gain public health experience with local health departments or non-profit organizations. We have found no published evaluations of PHTC field placement components. This may be because of their small size and unique nature. We designed and evaluated a 200-hour field placement program at an established Public Health Training Center. The evaluation included pre/post surveys measuring public health core competencies, and post-experience interviews. We found significant increases in three competency domains among trainees: policy development and program planning, communication skills, and community dimensions of practice. These outcomes contribute to an evidence base on the efficacy of PHTC field placement programs, and underscore their role in public health training.